AN ANALYSIS TO ROCK INSCRIPTIONS AND COPPER INSCRIPTIONS RECOVERED FROM THE FOURTH CENTURY AD TO THE FOURTEENTH CENTURY AD AS AN ANCIENT HISTORY OF ASSAMESE LANGUAGE - Chimpu Kalita; Lakhya Das (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Script separates written literature from Oral literature.The root of literature such as language that the root of the written language is such a script. The recovery of different Rock inscriptions engraved during the reign of Ashoka and his later kings helped to outline Indian past history. Similarly, the old philosophy of Assamese language is highlighted by Rock and copper inscriptions engraved on various kings. These inscriptions are recovered in various excavation sinews. The earliest rock inscription of inscriptions recovered so far dates back to the fourth century AD. So far, these Rock inscriptions and copperinscriptions have been able to be recovered from the fourth century AD to the 19th century.